Analisis Dampak Technostress terhadap Pembelajaran Praktikum Komputer - Mukhtar Mukhtar; Ismail Ismail (KITA Institute, 2019)
This study focuses on developing discontinuous use of computer intentions, namely behavioral intentions in the termination phase, in the context of software engineering lessons, where AMIK Indonesia educational institutions use curriculum with more practice than learning material and this shows a very important role, it is hoped this research also add insight and knowledge of researchers and computer practicum lecturers to control student behavior in absorbing material so that competencies are aligned with the aims of practicum learning so as to produce quality graduates. This research was conducted at AMIK Indonesia Banda Aceh. The population in this study were all active students at the University. With a purposive sampling technique involving 60 respondents through survey methods, and data analyzed with SmartPLS. The results of this study indicate the positive and negative impacts caused by computer practicum learning on student behavior at AMIK Indonesia. Practically, this research is useful in developing the design of computer lab learning governance which is the basis of material in institutions that involve a lot of practicum and computer usage. Improvement of computer practicum learning curriculum, in particular, is expected to have a large impact on the quality of these students but strengthening the material and reducing assignments by involving cases in the field will make students understand and easily learn the practical material itself.